The Independence of Woman Entrepreneurs in the Digital Era - Afina Aurellya Kamal; Dewi Sukmawati (Journal of Career and Entrepreneurship, 2022)
Entrepreneurship is currently one of the indicators that affect the economy of a country. Entrepreneurship is one of the jobs that many women do today. Independence is one of the success factors for women to do business or entrepreneurship in the digital era. This study aims to determine the effect of independence on entrepreneurship in the digital era. The object of this research is 30 woman entrepreneurs in the city of Malang. This research kind of explanatory research. The data analysis used is path analysis using the SmartPLS program. The results of this study indicate that independence has a positive and significant influence on women's entrepreneurship.